2019
DOI: 10.1080/20013078.2019.1706801
|View full text |Cite
|
Sign up to set email alerts
|

Activated human astrocyte‐derived extracellular vesicles modulate neuronal uptake, differentiation and firing

Abstract: Astrocytes in the central nervous system (CNS) provide supportive neural functions and mediate inflammatory responses from microglia. Increasing evidence supports their critical roles in regulating brain homoeostasis in response to pro-inflammatory factors such as cytokines and pathogen/damage-associated molecular pattern molecules in infectious and neurodegenerative diseases. However, the underlying mechanisms of the trans-cellular communication are still unclear. Extracellular vesicles (EVs) can transfer a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 47 publications
(66 reference statements)
4
109
0
Order By: Relevance
“…While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc. [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The EV cargo, packaged within relatively stable membrane-bound structures, is sheltered from degradation by the extracellular enzymes present in biological fluids, and may therefore maintain biological stability over comparatively long periods of time [38].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc. [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The EV cargo, packaged within relatively stable membrane-bound structures, is sheltered from degradation by the extracellular enzymes present in biological fluids, and may therefore maintain biological stability over comparatively long periods of time [38].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…Previous studies reported that EVs can affect the biological behaviours of recipient cells by transferring the encapsulated proteins [34,35]. Therefore, we prepared proteins from hESC-sEVs (Supplementary Figure 5), and then performed LC-MS/MS analysis to identify the protein contents of hESC-sEVs.…”
Section: Proteomics Analysis Of Hesc-sevsmentioning
confidence: 99%
“…The brain is capable to communicate with the rest of the body via transporting EVs to communicate healthy and disease states of the body (Gomez-Molina et al, 2019). Study of exosomes could increase our knowledge of astrocytes, their homeostasis, and metabolic regulating mechanisms since they are capable of transferring biological molecules from one cell to another (Fruhbeis et al, 2013;Silverman et al, 2019;Upadhya et al, 2020;You et al, 2020). Interestingly, miRNAs contained in the exosomes secreted by mouse astrocytes were different from the miRNAs that originally existed in mouse astrocytes.…”
Section: Importance Of Astrocyte-derived Evsmentioning
confidence: 99%
“…Physical or chemical microenvironmental changes affect astrocytes' growth and behavior. Changes in astrocytes alter the type of signals they release, therefore altering the microenvironment in a positive or negative manner (Paolicelli et al, 2019;Schiera et al, 2019;You et al, 2020). A study found a novel brain penetrant inhibitor that inhibited the release of vesicles in astrocytes (Rojas et al, 2019).…”
Section: The Relationship Between Astrocyte-derived Evs and Microenvimentioning
confidence: 99%
See 1 more Smart Citation